2017
DOI: 10.3324/haematol.2017.172866
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs of the nucleophosmin (NPM1) gene in acute myeloid leukemia

Abstract: In acute myeloid leukemia, there is growing evidence for splicing pattern deregulation, including differential expression of linear splice isoforms of the commonly mutated gene nucleophosmin (NPM1). In this study, we detect circular RNAs of NPM1 and quantify circRNA hsa_circ_0075001 in a cohort of NPM1 wild-type and mutated acute myeloid leukemia (n=46). Hsa_circ_0075001 expression correlates positively with total NPM1 expression, but is independent of the NPM1 mutational status. High versus low hsa_circ_00750… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 39 publications
(38 reference statements)
1
76
0
Order By: Relevance
“…Recently, evidence regarding the function of cir-cRNAs in AML patients has emerged. Hirsch et al delineated the expression pattern of nucleophosmin 1 (NPM1) circular RNA in different AML subgroups (13), L'Abbate et al observed significant overexpression of circPVT1 in amplicons involving chromosome band 8q24 in 23 cases of AML (AML-amp) cases (14), and Li et al reported that hsa_circ_0004277 can be a novel biomarker for AML treatment (4). To further investigate the roles of circRNAs in the development of AML, we first performed in silico analysis of the AML-specific circRNA microarray and ascertained the differentially expressed circRNA-DLEU2 in cytogenetically normal AML (CN-AML) patients compared with healthy controls.…”
mentioning
confidence: 99%
“…Recently, evidence regarding the function of cir-cRNAs in AML patients has emerged. Hirsch et al delineated the expression pattern of nucleophosmin 1 (NPM1) circular RNA in different AML subgroups (13), L'Abbate et al observed significant overexpression of circPVT1 in amplicons involving chromosome band 8q24 in 23 cases of AML (AML-amp) cases (14), and Li et al reported that hsa_circ_0004277 can be a novel biomarker for AML treatment (4). To further investigate the roles of circRNAs in the development of AML, we first performed in silico analysis of the AML-specific circRNA microarray and ascertained the differentially expressed circRNA-DLEU2 in cytogenetically normal AML (CN-AML) patients compared with healthy controls.…”
mentioning
confidence: 99%
“…Inappropriate activation of innate immune signaling in HSPCs and megakaryocytic abnormalities [117] Knockout in del(5q)MDS/AML Increase cell survival and proliferation of [118] [133] than in AML cell lines, and its expression was positively correlated with total NPM1 expression, but not with the status of NPM1 mutation [150]. Nevertheless, none of the current studies have elucidated the role of circRNA in AML pathogenesis.…”
Section: Aberrant Circrna Expression Levels In Acute Myeloid Leukemiamentioning
confidence: 87%
“…Because the presence of circRNAs has also been detected in extracellular vesicles [91], these circRNAs may modulate TME through cell-to-cell communication, although this is yet to be experimentally proven. Another circRNA, hsa_ circ_0075001, has been detected in AML where its expression positively correlated with total NPM1 expression [60]. AML patients carrying a high expression of hsa_circ_0075001 had lower expression of components of the Toll-like receptor signaling pathway, suggesting that this circRNA might be involved in the modulation of the immune response in AML [60].…”
Section: Role Of Non-coding Rnas In Immune Modulation In Leukemiamentioning
confidence: 99%
“…Another circRNA, hsa_ circ_0075001, has been detected in AML where its expression positively correlated with total NPM1 expression [60]. AML patients carrying a high expression of hsa_circ_0075001 had lower expression of components of the Toll-like receptor signaling pathway, suggesting that this circRNA might be involved in the modulation of the immune response in AML [60]. Another cir-cRNA, circMYBL2, which is derived from the cellcycle checkpoint gene MYBL2, has been reported to be highly expressed in FLT3-ITD mutation-positive AML patients [235].…”
Section: Role Of Non-coding Rnas In Immune Modulation In Leukemiamentioning
confidence: 99%